Safety of COVID-19 vaccines in subjects with solid tumor cancers receiving immune checkpoint inhibitors - Danielle Gilbert; Junxiao Hu; Theresa Medina; Elizabeth R. Kessler; Elaine T. Lam (Taylor & Francis Group, 2023)
The incidence of severe immune-related adverse events (irAEs) in cancer subjects receiving immune checkpoint inhibitors (ICIs) following COVID-19 vaccination and the relationship between the incidence of severe irAE and the interval between COVID-19 vaccination and ICI dose have not been established. We performed a retrospective study evaluating the incidence of irAEs in solid tumor subjects receiving ICI therapy who received any COVID-19 vaccinations since FDA authorization. irAEs were defined as severe with one or more grade 3 or above events (CTCAE v5.0), multiple organ involvement, or requiring hospitalization for management. Two hundred and eighty-four subjects who received COVID vaccinations from December 2020 and February 2022 were included in this analysis [median age at vaccination 67 years (IQR 59.0-75.0); 67.3% male]. Twenty-nine subjects (10.2%) developed severe irAEs, of which 12 subjects (41.4%) received ICI monotherapy, 10 subjects (34.5%) received combination ICI therapy with nivolumab and ipilimumab, and 7 subjects (24.1%) received ICI plus VEGFR-TKI therapy. Hospitalization occurred in 62% of subjects with severe irAEs, with a median duration of 3 days (IQR: 3.0-7.5 days). Immunosuppressive therapy was required in 79.3%, with a median duration of 103 days (IQR: 42.0-179.0). ICI therapy was discontinued in 51.7% of subjects with severe irAE; dosing was held or interrupted in 34.5%. Among severe irAEs, the median interval between vaccination and ICI treatment closest to the occurrence of severe irAE was 15.5 days (IQR: 10.0-23.0). In solid tumor cancer subjects receiving ICIs, COVID-19 vaccination is not associated with an increased incidence of severe irAEs compared to historical data and may be safely administered during ICI cancer therapy in subjects who lack contraindications.